S2k guideline for treatment of cutaneous lupus erythematosus – guided by the European Dermatology Forum (EDF) in cooperation with the European Academy of Dermatology and Venereology (EADV). (20th December 2016) - Kuhn, A.; Aberer, E.; Bata‐Csörgő, Z.; Caproni, M.; Dreher, A.; Frances, C.; Gläser, R.; Klötgen, H.‐W.; Landmann, A.; Marinovic, B.; Nyberg, F.; Olteanu, R.; et al.
Abstract: Cutaneous lupus erythematosus (CLE) is a rare inflammatory autoimmune disease with heterogeneous clinical manifestations. To date, no therapeutic agents have been licensed specifically for patients with this disease entity, and topical and systemic drugs are mostly used 'off‐label'. The aim of the present guideline was to achieve a broad consensus on treatment strategies for patients with CLE by a European subcommittee, guided by the European Dermatology Forum (EDF) and supported by the European Academy of Dermatology and Venereology (EADV). In total, 16 European participants were included in this project and agreed on all recommendations. Topical corticosteroids remain the mainstay of treatment for localized CLE, and further topical agents, such as calcineurin inhibitors, are listed as alternative first‐line or second‐line topical therapeutic option. Antimalarials are recommended as first‐line and long‐term systemic treatment in all CLE patients with severe and/or widespread skin lesions, particularly in patients with a high risk of scarring and/or the development of systemic disease. In addition to antimalarials, systemic corticosteroids are recommended as first‐line treatment in highly active and/or severe CLE. Second‐ and third‐line systemic treatments include methotrexate, retinoids, dapsone and mycophenolate mofetil or mycophenolate acid, respectively. Thalidomide should only be used in selected therapy‐refractory CLE patients, preferably in addition to antimalarials. Several new therapeutic options, such as B‐cell‐ or interferon α‐targeted agents, need to be further evaluated in clinical trials to assess their efficacy and safety in the treatment of patients with CLE.